Peningkatan Pengetahuan Pencegahan Stunting Melalui Edukasi Kesehatan di Posyandu Sentosa, Desa Jati Baru, Riau - Ramadhani Al Adn, Nadhifa Seruni; Istiqomah, Nurul; Zulfatunnisa, Nevia (Universitas Pahlawan Tuanku Tambusai, 2025)
Stunting is a chronic nutritional problem that remains a major public health challenge in Indonesia, including in Siak Regency. This activity aimed to analyze the effectiveness of stunting education in improving mothers’ knowledge of toddlers at Posyandu Sentosa, Jati Baru Village. The method used was health education with pre-test and post-test questionnaires administered to 25 respondents selected through purposive sampling. The instrument used was a validated and reliable questionnaire on knowledge about stunting. The educational session was delivered using PowerPoint media through direct presentation and interactive discussion methods. The results showed an increase in mothers’ knowledge after the education, with the average pre-test score of 7.44 rising to 10.40 on the post-test (a difference of 2.96 points). This finding indicates that the educational activity effectively improved mothers’ understanding of balanced nutrition, proper parenting, and healthy living behaviors. In conclusion, stunting prevention education positively influences mothers’ knowledge and strengthens the role of Posyandu as a strategic platform for promotive and preventive efforts at the village level.